Assessment of awareness and action towards signs and symptoms of stroke among lay public in Kuantan, Malaysia: A cross-sectional study - Mohammed Ahmed, Abdul Kareem; Ahmed, Abdullah Abdulmajid Abdo; Fata Nahas, Abdul Rahman; Zawiah, Mohammed; Jamshed, Shazia Qasim; Mohamed Ibrahim, Mohamed Izham (Longe Medikal Sdn Bhd, 2020)
Background: Stroke remains one of the leading causes of mortality and disability in both developing and developed countries. Lack of awareness towards signs and symptoms of stroke leads to delayed presentation to the hospital, contributing towards increased morbidity and mortality. This study aimed to assess the awareness of and action towards signs and symptoms of a stroke. Methods: A cross-sectional study interview-based survey was performed among 393 lay public (age range: 18-64 years old) in states of Pahang, Kuantan city, Malaysia from June to September 2019. Chi-square tests were used to assess the knowledge of differences between participants with good education and income and those with low education and incomes. as well as logistic regression to obtain the factors effecting to the knowledge of stroke symptoms. Results: Majority of respondents (n=309,78,6%) identified sudden face, arms and leg numbness, whereas (n=165,42%) of them identified problems in vision as stroke symptoms. However, (n=39,10.4%) were unaware of any symptoms, while (n=117,30%) identified appropriate action. Furthermore, (n=349, 88.8%) recognized at least one stroke symptom,(n=108, 27.5%) of them identified all five stroke symptoms, and (n=37,9.4%) of individuals had excellent awareness (aware of all five stroke symptoms and appropriate action “calling an ambulance”). Multivariable logistic regression shows that individuals aged 18-45 years (OR=0.054, 95% Cl=0.006-0.500, p=0.010), self-employed (OR=12.430, 95% Cl=1.372-31.908, p=0.028), those who were diagnosed with hypertension (OR=0.129, 95% Cl=0.025-0.673, p=0.015) and students (OR=35.945. 95% Cl=1.745-740.615, p=0.020) were more likely to recognize all the five-stroke symptoms and appropriate action. Conclusion: The awareness and action towards signs and symptoms of a stroke are poor among the lay public in Kuantan, Malaysia. Therefore, the findings of this study would be a baseline for program interventions that focus on public awareness and policy development on stroke management.